Project management principles special aspects - V. V. Eremin; D. V. Firsov; T. K. Chernysheva (Управление)
The modern vector of development of the national economy and its focus on programme-targeted organisation makes us consider the principles of organisation in public administration in a new way. Modern conditions and principles of public administration require the adaptation of fundamentally new methodological guidelines that can not only manage existing systems, but also stimulate the emergence of fundamentally new economic and social realities. Currently, financing of state programme takes about 70 % of the federal budget, however, the actual implementation of the laid down plans of state programme is far behind the planned targets.Within the international practice of economies with a related organisational structure focused on the implementation of large programme projects, the focus on project management begins to occupy a dominant position in the practice of public management, especially in the field of strategic development.The article studies the special aspects of the project management formation and its scaling at the national level. The paper analyses the experience of implementing the principles of project management in public administration. At the same time, the authors highlight the main fundamental provisions of the successful implementation of projects and determine the key directions for improving the efficiency of project management.